2014
DOI: 10.1287/orsc.2013.0844
|View full text |Cite
|
Sign up to set email alerts
|

Firms, Markets, and the State: Institutional Change and Manufacturing Sector Profitability Variances in India

Abstract: W e assess absolute magnitudes, relative importance, and intertemporal differences in firm, industry, and business group effects in explaining the variance of Indian manufacturing firms' profitability over the 26-year period between 1980-1981 and 2005-2006. We stratify the data by institutional phases to place emphasis on the role of changing institutional factors in an emerging economy: first as a regime of command and control transits to partial liberalization (between 1985 and 1991) and then to an open comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 85 publications
3
40
0
Order By: Relevance
“…The differences between emerging and developed economies are so profound that they can only result in unequal growth opportunities for firms (Majumdar and Bhattacharjee, ; Peng, ; Tong et al , ). Indeed, Diaz‐Hermelo and Vassolo () proposed that persistent superior economic performance is more difficult for firms in emerging economies.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between emerging and developed economies are so profound that they can only result in unequal growth opportunities for firms (Majumdar and Bhattacharjee, ; Peng, ; Tong et al , ). Indeed, Diaz‐Hermelo and Vassolo () proposed that persistent superior economic performance is more difficult for firms in emerging economies.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In such conditions, firms tend to revert back on their idiosyncratic competencies and strategies, rather than being reliant on informal markets and affiliations (Chakrabarti et al, 2007). Indeed, Majumdar and Bhattacharjee (2014) showed that the contestable climate of institutions in transition inspire idiosyncratic capability development and new firm strategic initiatives.…”
Section: Exploring the Country Effect In Emerging Economies During Rementioning
confidence: 99%
“…Emerging economies such as China and India are unique and hence are valuable contexts for research (Luo and Tung, 2007). While a number of interesting studies have been conducted leveraging the unique context of China (e.g., Child, 1996;Nee, 1992;Luo and Peng, 1999;Peng and Luo, 2000;Tsui et al, 2004), India's potential as a valuable research context is yet to be fully realized (Chari and David, 2012;Khanna and Palepu, 2000;Majumdar and Bhattacharjee, 2014). A broad objective of the India special issue in Long Range Planning is therefore to highlight how India constitutes a valuable context to address a number of interesting research questions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows indicative trajectories of broad-scope reforms in India, comprised of product market reforms (starting in 1991), capital market reforms (starting in 1999-2000) and legal reforms (Chari & David, 2012;Popli & Sinha, 2014). Each set of reforms represents a shock (Majumdar & Bhattacharjee, 2013) and is followed by more progressive reforms.…”
Section: Matching Timing Of Initiationmentioning
confidence: 99%